2009
DOI: 10.1093/ejo/cjn083
|View full text |Cite
|
Sign up to set email alerts
|

Dental Aesthetic Index scores and perception of personal dental appearance among Turkish university students

Abstract: The aim of this study was to investigate the relationship between Turkish university students' awareness of malocclusion, their satisfaction with their personal dental appearance, and the severity of their occlusal irregularities. The sample consisted of 841 randomly selected university students, 522 (62.1 per cent) males and 319 (37.9 per cent) females, aged 17-26 years (mean age, 21.91+/-1.92 years). A pre-tested questionnaire was used to assess the subjects' awareness of malocclusion and satisfaction with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
3
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 23 publications
6
36
3
7
Order By: Relevance
“…O DAI foi indicado pela Organização Mundial de Saúde (OMS) como forma de avaliar a presença de oclusopatias a nível populacional, sendo caracterizado pela combinação de medidas as quais expressam a condição oclusal do indivíduo e sua necessidade de tratamento 17 . Tal índice vem sendo amplamente utilizado em estudos populacionais em diferentes populações 5,[18][19][20] , sendo indicado e aplicado, principalmente, para crianças de 12 anos de idade. Dessa forma, este instrumento tem sido utilizado por estudos prévios com intuito de estimar os diferentes níveis de gravidade da maloclusão [18][19][20] , assim como a necessidade de tratamento ortodôntico 5 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…O DAI foi indicado pela Organização Mundial de Saúde (OMS) como forma de avaliar a presença de oclusopatias a nível populacional, sendo caracterizado pela combinação de medidas as quais expressam a condição oclusal do indivíduo e sua necessidade de tratamento 17 . Tal índice vem sendo amplamente utilizado em estudos populacionais em diferentes populações 5,[18][19][20] , sendo indicado e aplicado, principalmente, para crianças de 12 anos de idade. Dessa forma, este instrumento tem sido utilizado por estudos prévios com intuito de estimar os diferentes níveis de gravidade da maloclusão [18][19][20] , assim como a necessidade de tratamento ortodôntico 5 .…”
Section: Introductionunclassified
“…Tal índice vem sendo amplamente utilizado em estudos populacionais em diferentes populações 5,[18][19][20] , sendo indicado e aplicado, principalmente, para crianças de 12 anos de idade. Dessa forma, este instrumento tem sido utilizado por estudos prévios com intuito de estimar os diferentes níveis de gravidade da maloclusão [18][19][20] , assim como a necessidade de tratamento ortodôntico 5 . A prevalência da maloclusão entre crianças de 12 anos tem variado em diferentes países, com taxas próximas aos 30% em países como Índia 20 e Espanha 21 .…”
Section: Introductionunclassified
“…Other studied like Nihal et al 25 revealed found a significant negative relationship but weak for awareness Turkish university students' of malocclusion and satisfaction with the appearance of teeth at different levels of severity of malocclusion. Results of the study showed that age had an impact on satisfaction and gender-DAI score variation.…”
Section: "Unlike the Index Of Orthodontic Treatmentmentioning
confidence: 85%
“…Despite the increasing attention drawn to the field of quality of life studies, orthodontic treatment need and patient triage is often carried out using clinically defined norms in Turkey. [24][25][26][27] Dogan et al…”
Section: Discussionmentioning
confidence: 99%